Molecular Control of Sucrose Utilization in Escherichia coli W, an Efficient Sucrose-Utilizing Strain - Sabri, Suriana (American Society for Microbiology, 2013)
Sucrose is an industrially important carbon source for microbial fermentation. Sucrose utilization in Escherichia coli, however, is poorly understood, and most industrial strains cannot utilize sucrose. The roles of the chromosomally encoded sucrose catabolism (csc) genes in E. coli W were examined by knockout and overexpression experiments. At low sucrose concentrations, the csc genes are repressed and cells cannot grow. Removal of either the repressor protein (cscR) or the fructokinase (cscK) gene facilitated derepression. Furthermore, combinatorial knockout of cscR and cscK conferred an improved growth rate on low sucrose. The invertase (cscA) and sucrose transporter (cscB) genes are essential for sucrose catabolism in E. coli W, demonstrating that no other genes can provide sucrose transport or inversion activities. However, cscK is not essential for sucrose utilization. Fructose is excreted into the medium by the cscK-knockout strain in the presence of high sucrose, whereas at low sucrose (when carbon availability is limiting), fructose is utilized by the cell. Overexpression of cscA, cscAK, or cscAB could complement the WΔcscRKAB knockout mutant or confer growth on a K-12 strain which could not naturally utilize sucrose. However, phenotypic stability and relatively good growth rates were observed in the K-12 strain only when overexpressing cscAB, and full growth rate complementation in WΔcscRKAB also required cscAB. Our understanding of sucrose utilization can be used to improve E. coli W and engineer sucrose utilization in strains which do not naturally utilize sucrose, allowing substitution of sucrose for other, less desirable carbon sources in industrial fermentations.